Radioactive soil contamination of Barguzin biospherereserve (Buryatia); 7th International Symposium on IN SItu NUclear Metrology as a tool for radioecology - INSINUME 2017, 24-28 April 2017, Ohrid, Macedonia - Galushkina D. N. Darjya Nikolaevna (2017, 2017)
В фонде НТБ ТПУ отсутствует